Creation of an algorithm for the optimal functioning of an underground gas storage station - B.U.Shomirzaev (Zien Journals, 2022)
The article deals with the creation of an algorithm optimal control of the technological parameters of an underground gas storage station, the relevance of solving the problem of creating automatic control systems for automating the control and management of technological parameters. According to the author's conclusion, the use of the optimal control algorithm for an underground gas storage station improves station performance.
Keywords: gas pipeline; injection; regulation; underground gas storage